Strategies and tactics in organic synthesis. Volume 8 - Harmata, Michael, 1959- (Amsterdam ; Boston : Academic Press, 2012)
A classic in the area of organic synthesis, Strategies and Tactics in Organic Synthesis provides a forum for investigators to discuss their approach to the science and art of organic synthesis. Rather than a simple presentation of data or a second-hand analysis, this book vividly demonstrates through first hand accounts how synthesis is really done and how by discovering new reactions, creating new designs and building molecules with atom and step economies, the advancement of the science of organic synthesis is providing solutions through function to create a better world. Presents state-of-the-art developments in organic synthesisProvides insight and offers new perspective to problem-solvingWritten by leading experts in the field.
Title from publisher's Web site; (ScienceDirect, viewed on Aug. 8, 2012).
Includes bibliographical references and index.
Keywords: Organic compounds -- Synthesis; SCIENCE -- Chemistry -- Organic; Organic compounds -- Synthesis